Entry strategy of global corporations on the markets of non EU countries ( India) - Mehra, Shrey; Pichanič, Mikuláš, 1942-; Říha, David; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
The primary objective of this master thesis is to explore and analyze the market entry strategies of multinational corporations in India. While the secondary objectives are to analyze the retail industry of India and market entry strategy of Walmart India. The outcome of this thesis is a decision on the market perspectives and potential opportunities for the company in the coming years. The conclusion is based on the analysis of the current market and political scenario; investment regulations, competition analysis. The thesis is divided into three chapters and the conclusion thereafter.The First chapter explains about the economy and industry (retail) analysis, while the second chapter consist of the theoretical part is concentrated on the market opportunities for the global retail players and the theoretical aspects of market entry strategies, with a case study of each entry strategies. In the third chapter, I started with an analysis of Walmart company worldwide and then explained about the history and current situation of Walmart in India, while the key talking point in this chapter is about the change in their market entry strategy in 2013.
Vedoucí práce: Mikuláš Pichanič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses